The Estevan Strike and Riot of 1931: Remembering One of the Most Important Strikes in Canadian History - Makahonuk, Glen (Briarpatch, 1997)
The MWUC was an affiliate of the revolutionary Workers Unity League (WUL) which promoted the class struggle. On August 25, 1931 James Sloan, president of the MWUC, arrived in [Estevan] and organized a meeting. Practically every miner in the field showed up. After a rousing speech on the miners' plight and the objectives of the MWUC [Mine Workers' Union of Canada], more than 600 miners signed up. Government officials and the coal owners saw the danger in these demands and attempted to reduce the threat by bringing more RCMP into the area. When negotiations commenced on October 19, L. Maurice, MWUC vice - president, who had travelled from Calgary to act as an advisor to the miners, was expelled from the meeting. Although the coal owners refused to recognize the MWUC, they did agree to recognize the pit committees and granted a number of other demands for better working conditions and wages. The Saskatchewan Federation of Labour is commemorating the 1931 strike and riot in order to honour these miners and educate the public about our labour history. The public event will take place at the miners' coal car by the Court House in downtown Estevan on May 10, 1997.
Keywords: 1914 1938; Canadian history; Coal mines; Coal mining; History; Labor unions; Political Science; Strikes